2022
DOI: 10.1021/acs.iecr.2c01976
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Interaction and Diffusion for Dimethyl Disulfide Adsorption on Cu-BTC Frameworks via Low Transition-Metal Doping

Abstract: Metal–organic frameworks (MOFs) have been finding increasing involvements in the capture of environmentally unfriendly compounds including volatile organosulfides contained in a wide range of energy sources owing to their editable structures. In this study, modulation of interaction and diffusion for sulfide adsorption on Cu-BTC frameworks was achieved via doping a series of transition-metal ions (Ni, Co, Fe, Zn, and Cr) at a low content through post-synthesis in an ethanol system. Synthesized samples were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The adsorption capacities of 1-hexene and n -hexane were 152.7and 15.7 mg/g, with the highest 1-hexene/ n -hexane selectivity being 9.74. Zhu et al used a solvothermal approach to optimize the synthesis of Cu-BTC and discovered that its adsorption capabilities for 1-hexene and n -hexane were 122.31 and 18.95 mg/g, respectively, with a selectivity of 6.45. Furthermore, when the sample was modified by acetic acid, the adsorption amount of 1-hexene increased to 187.90 mg/g, while that of n -hexane decreased from 18.95 to 10.75 mg/g, resulting in an improvement in selectivity from 6.45 to 17.48.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption capacities of 1-hexene and n -hexane were 152.7and 15.7 mg/g, with the highest 1-hexene/ n -hexane selectivity being 9.74. Zhu et al used a solvothermal approach to optimize the synthesis of Cu-BTC and discovered that its adsorption capabilities for 1-hexene and n -hexane were 122.31 and 18.95 mg/g, respectively, with a selectivity of 6.45. Furthermore, when the sample was modified by acetic acid, the adsorption amount of 1-hexene increased to 187.90 mg/g, while that of n -hexane decreased from 18.95 to 10.75 mg/g, resulting in an improvement in selectivity from 6.45 to 17.48.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, when the sample was modified by acetic acid, the adsorption amount of 1-hexene increased to 187.90 mg/g, while that of n-hexane decreased from 18.95 to 10.75 mg/g, resulting in an improvement in selectivity from 6.45 to 17.48. Qian et al 29 discovered that the ethanol/ transition metal system may convert some Cu(II) in Cu-BTC to Cu(I) while altering the pore shape to improve the adsorption performance of dimethyl disulfide (DMDS).…”
Section: ■ Introductionmentioning
confidence: 99%
“…192 The interaction energy calculation results showed that all the metal-doped MOFs had more exothermic energies for interacting with DMDS than the original Cu-BTC, indicating stronger host-guest interactions within the modied MOFs. 192 Additionally, computational simulation results demonstrated that the captured DMDS molecules were positioned near the doped metal ions (Fig. 21), which was consistent with the batch adsorption experiment results.…”
Section: Computational Chemistrymentioning
confidence: 94%
“…A series of metal-doped (Co, Fe, Zn, Cr, Ni) Cu-BTCs were developed by PSM for dimethyl disulfide (DMDS) adsorption. 192 Computational simulation was used to elucidate the effect of metal doping on the DMDS affinity of the modified MOFs. 192 The interaction energy calculation results showed that all the metal-doped MOFs had more exothermic energies for interacting with DMDS than the original Cu-BTC, indicating stronger host–guest interactions within the modified MOFs.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation